Preparation method of acidic solid catalyst with self-contained microporous polymer
By subjecting the self-porous polymer PIM-1 to amino reduction and sulfonic acid group sulfonation modification, an acidic solid catalyst H-PIM-PS with high specific surface area and sulfonic acid groups was prepared, solving the problem of existing catalysts. The problems of difficult recycling and poor reusability have enabled the production of highly efficient catalytic biodiesel.
Patent Information
- Application Number
- CN202410532496.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-29
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-04-29
AI Technical Summary
The existing catalysts used for the production of biodiesel in esterification reactions have problems such as equipment corrosion, difficulty in recycling, environmental pollution and poor reusability.
Adopt self-use microporous polymer PIM-1 as the starting material, to restore the modification of sulfonate sulfonate through hydrophilicon, and prepare a high-pellet polymer acidic solid catalyst with a high ratio and sulfonic acid group H-PIM-PS.
This catalyst has high catalytic activity, good stability and excellent reuse, which can effectively improve the production efficiency of biological diesel and the feasibility of large -scale production.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and in particular relates to a self-microporous polymer acidic solid catalyst and a preparation method thereof, and application in the production of biodiesel by catalyzing esterification reactions. Background Art
[0002] Biodiesel, as a green and renewable energy source, is a major energy source that can replace traditional fossil fuels. Acid-catalyzed esterification reaction is an important way to produce biodiesel. At present, the catalysts used for esterification reaction to produce biodiesel are mostly inorganic acid-base catalysts such as concentrated sulfuric acid and sodium hydroxide. The use of such catalysts will cause equipment corrosion, recycling difficulties, environmental pollution and other problems, affecting the large-scale production of biodiesel. In recent years, ionic liquids, as a new type of green and efficient catalyst, can be used to replace traditional catalysts to catalyze the production of biodiesel. However, it has problems such as difficulty in recycling. The problem of recycling difficulty is solved by loading ionic liquids on polymers, but it has disadvantages such as small specific surface area and low catalytic activity. At the same time, the proton acid that exerts catalytic performance in the production of biodiesel using immobilized ionic liquids is mainly obtained by adding acid. During the reaction, the proton acid will be lost in the reaction with the added acid, resulting in reduced activity and poor reusability.
[0003] The British journal Fuel (Fuel, 2017, 188: 483-488) reported an acidic ionic liquid catalyst for catalyzing the transesterification reaction of rapeseed oil to produce biodiesel. First, an imidazole ionic liquid catalyst was prepared by using imidazole and 1,3-propane sultone for sulfonation reaction, and then sulfuric acid was added to acidify it, and it was used for transesterification reaction. The yield of FAME was the highest under the conditions of reaction temperature of 130°C, 1-butylsulfonic acid-3-methylimidazolium hydrogen sulfate ([BSO3HMIM][HSO4]) mass fraction of 2%, alcohol-oil molar ratio of 12:1, and reaction time of 3h. Under the optimal conditions, the yield of FAME can reach up to 100% with [BSO3HMIM][HSO4] as catalyst. However, its reaction conditions are harsh, difficult to recover, and poor reproducibility.
[0004] The British Journal of Energy Conversion and Management (Energy Conversion and Management, 2017, 231: 458-467) reported an ionic liquid catalyst, namely 3-(2,3-dihydroxypropyl)-1-methyl-1H-imidazole-3-hydroxide (DFImIL-OH - ) and poly(3-benzyl-1-(4-(sec-butyl)benzyl)-1H-benzimidazole-3-hydroxide)(PIL(OH - )). The study found that among all the synthesized catalysts, benzimidazole Ionic liquid catalyst (BBAIL) is the best catalyst for catalyzing castor oil transesterification to produce biodiesel. When the molar ratio of methanol to castor oil is 12:1, the reaction temperature is 40°C, the reaction time is 14h, and the catalyst dosage is 5wt%, the biodiesel yield reaches 96%. The BBAIL catalyst synthesized in this study is difficult to recycle and has poor recyclability.
[0005] In order to solve the above problems, it is of great significance for the production of biodiesel to develop a self-microporous polymer acidic solid catalyst with good catalytic performance, good stability and easy recycling and reuse. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a self-microporous polymer acidic solid catalyst, in order to overcome the technical defects of the existing catalysts used for esterification reaction to produce biodiesel.
[0007] To achieve the above object, the present invention adopts the following technical solution:
[0008] A preparation method of a self-microporous polymer acidic solid catalyst comprises the following steps: dissolving a self-microporous polymer PIM-1 in an organic solvent, adding hydrazine hydrate to the PIM-1 solution for reduction reaction after the self-microporous polymer PIM-1 is completely dissolved, synthesizing a self-microporous polymer (H-PIM-1) with an amino group, reacting the H-PIM-1 with sultone to synthesize a self-microporous polymer with a sulfonic acid group, and then precipitating the reaction product, repeatedly washing and drying the reaction product, and finally obtaining the self-microporous polymer acidic solid catalyst (H-PIM-PS).
[0009] The structural formula of the PIM-1 is shown below:
[0010]
[0011] The H-PIM-1 is composed of repeating units containing amino groups and repeating units without amino groups, and the structural formula is as follows:
[0012]
[0013] Where n = 0.2% - 100%, that is, the reduction degree of H-PIM-1.
[0014] The H-PIM-PS is composed of repeating units containing sulfonic acid groups and repeating units without sulfonic acid groups, and its structural formula is as follows:
[0015]
[0016] Where n = 0-100%, that is, the sulfonation degree of H-PIM-PS.
[0017] The organic solvent used to dissolve H-PIM-1 is tetrahydrofuran, 1,4-dioxane or N,N-dimethylformamide.
[0018] The concentration of the H-PIM-1 is 10 wt % to 60 wt %.
[0019] The sultone is 1,3-propanesultone or 1,4-butanesultone.
[0020] The molar ratio of the repeating unit with amino group to sultone contained in the H-PIM-1 is 1:1-20.
[0021] The reaction temperature of the H-PIM-1 and sultone is 30° C.-70° C., and the reaction time is 4 h-24 h.
[0022] The beneficial effects of the present invention are as follows: the present invention uses a self-microporous polymer PIM-1 with a high specific surface area as a starting material, uses hydrazine hydrate to reduce the nitrile group contained in PIM-1, obtains a self-microporous polymer with an amino group (H-PIM-1), and then uses sultone to sulfonate the H-PIM-1 to obtain a self-microporous polymer acidic solid catalyst with a sulfonic acid group. The self-microporous polymer acidic solid catalyst provided by the present invention has the following significant advantages: (1) the self-microporous polymer has an ultra-high specific surface area, which can provide more contact area with the reactant and improve the catalytic activity; (2) the sulfonic acid group is introduced into the self-microporous polymer through a chemical reaction, and the stability is good; (3) the modified catalyst is solid, easy to separate and recover, and has excellent reusability (4) the sulfonation degree can be controlled by adjusting the input amount of 1,3-propane sultone, and the self-microporous polymer acidic solid catalyst with the best performance can be selected for biodiesel production. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 3,3',3'-tetramethyl-1,1'-spirobiindane (TTSBI) synthesized in Example 1 1 H NMR spectrum.
[0024] Figure 2 PIM-1 synthesized in Example 1 1 H NMR spectrum.
[0025] Figure 3 FT-IR spectra of PIM-1, H-PIM-1, and H-PIM-PS synthesized in Example 1. DETAILED DESCRIPTION
[0026] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.
[0027] The chemical reagents used in the embodiments of the present invention are all commercially available.
[0028] Example 1
[0029] 19.86g of catechol was dissolved in a mixed solution of 44mL of hydrobromic acid and 40mL of glacial acetic acid. After complete dissolution, 28mL of acetone was added dropwise and reacted at 120℃ for 12h to obtain a reddish-brown reaction solution. The reddish-brown reaction solution was poured into a large amount of deionized water to precipitate a brown solid, which was repeatedly washed with glacial acetic acid to obtain a white product, namely TTSBI, and placed in an oven at 80℃ for drying. The synthesis reaction of PIM-1 adopts a high-temperature method. 10.212g of dry TTSBI, 6.027g of tetrafluoroterephthalonitrile and 10.365g of K2CO3 were added to the flask in sequence, and then 70mL of anhydrous N-methylpyrrolidone was added to start stirring, and it was quickly placed in an oil bath at 155℃, and then 30mL of anhydrous toluene was added. The reaction was reacted for 6h under a nitrogen atmosphere. As the reaction time increased, the viscosity of the reaction system gradually increased, and a bright yellow viscous mixed solution was finally obtained. After the reaction was completed, the mixed solution was poured into methanol to obtain a bright yellow block solid, which was washed with methanol and water several times. After drying, the product was dissolved in chloroform, filtered with non-woven fabric, and then the solution was precipitated in methanol, and the process was repeated several times to obtain the final PIM-1, which was dried in a vacuum oven at 80°C for 16 hours. 2g of PIM-1 was dissolved in 100mL of tetrahydrofuran and placed in a constant temperature water bath at 60°C, 40mL of hydrazine hydrate and 0.2g of palladium carbon were added, and nitrogen was passed through at 60°C for 24 hours. After the reaction, the palladium carbon and the reaction solution were separated by filtration, and the reaction solution was poured into methanol to precipitate a yellow solid to obtain a self-microporous polymer with amino groups (H-PIM-1), which was then repeatedly washed with methanol and dried in an oven at 80°C for 12 hours.
[0030] Dissolve 1g of the dried microporous polymer H-PIM-1 in 50mL of tetrahydrofuran and slowly add it to 0.2376g of 1,3-propanesulfonate using a constant pressure dropping funnel, and react at 60°C for 24h. After the reaction, pour the reaction solution into methanol to precipitate a brown solid. Wash it repeatedly with methanol and dry it in an oven at 80°C for 12h. After drying, soak it in a 0.1mol / L hydrochloric acid aqueous solution for 12h to ensure that the sulfonic acid group is converted to H + The sulfonated microporous polymer H-PIM-PS was then washed with deionized water until neutral, and finally dried in a 60°C constant temperature drying oven for 12 hours. The acid exchange capacity of H-PIM-PS was measured to be 1.03 mmmol / g.
[0031] The H-PIM-PS prepared in this embodiment is used as a catalyst to catalyze the esterification reaction of oleic acid and methanol to produce biodiesel, so as to evaluate the performance of H-PIM-PS in catalytic production of biodiesel. Specifically, 3g of oleic acid is mixed with 4.078g of methanol (the molar ratio of methanol to oleic acid is 12:1), and then 0.35g of catalyst H-PIM-PS (mass concentration is 5wt%) is added, the reaction temperature is 70°C, and the reaction time is 2h. Biodiesel is produced under this condition. After the reaction is completed, solid H-PIM-PS is recovered by filtration. The experimental results show that the conversion rate of oleic acid is 72.5%, indicating that the catalyst H-PIM-PS-1 has excellent catalytic performance. H-PIM-PS-1 was subjected to 6 repeated experiments for preparing biodiesel by the above-mentioned esterification reaction. The results show that after six repeated uses, the conversion rate of oleic acid remains unchanged, indicating that H-PIM-PS has excellent stability. In addition, the recovery rate of H-PIM-PS after the reaction is greater than 99%, indicating that H-PIM-PS has excellent reusability.
[0032] Example 2
[0033] H-PIM-PS was prepared using the same amino self-microporous polymer H-PIM-1 as in Example 1. 1 g of H-PIM-1 was dissolved in 50 mL of tetrahydrofuran and slowly added to 1.1881 g of 1,3-propane sultone using a constant pressure dropping funnel. The mixture was reacted at 30°C for 4 h. After the reaction was completed, the mixture was poured into methanol for precipitation. After being repeatedly washed with methanol, the mixture was soaked in a 0.1 mol / L hydrochloric acid aqueous solution for 12 h to ensure that the sulfonic acid groups were H + The prepared catalyst H-PIM-PS was placed in a constant temperature drying oven at 60°C and dried for 12 hours. Finally, the self-microporous polymer acidic solid catalyst H-PIM-PS was obtained. The acid exchange capacity of H-PIM-PS was measured to be 0.76mmmol / g.
[0034] The catalyst H-PIM-PS prepared in this example was tested for its catalytic performance in catalyzing the production of biodiesel in an esterification reaction under the same reaction conditions as in Example 1. The results showed that the conversion rate of oleic acid was 66.4%. Then, H-PIM-PS was subjected to 6 repeated experiments of preparing biodiesel by the esterification reaction described above. The experimental results showed that the conversion rate of oleic acid remained unchanged, indicating that H-PIM-PS has excellent stability. At the same time, the recovery rate of H-PIM-PS after the reaction is greater than 99%, indicating that H-PIM-PS has excellent reusability.
[0035] Example 3
[0036] H-PIM-PS was prepared using the same amino self-microporous polymer H-PIM-1 as in Example 1. 1 g of H-PIM-1 was dissolved in 50 mL of 1,4-dioxane and slowly added to 2.3762 g of 1,3-propane sultone using a constant pressure dropping funnel. The mixture was reacted at 40°C for 8 h. After the reaction was completed, the mixture was poured into methanol for precipitation. After being repeatedly washed with methanol, the mixture was soaked in a 0.1 mol / L hydrochloric acid aqueous solution for 12 h to ensure that the sulfonic acid groups were H + The prepared catalyst H-PIM-PS was placed in a constant temperature drying oven at 60°C and dried for 12 hours. Finally, the self-microporous polymer acidic solid catalyst H-PIM-PS was obtained. The acid exchange capacity of H-PIM-PS was measured to be 1.22mmmol / g.
[0037] The catalyst H-PIM-PS prepared in this example was tested for its catalytic performance in catalyzing the production of biodiesel in an esterification reaction under the same reaction conditions as in Example 1. The results showed that the conversion rate of oleic acid was 86.4%. Then, H-PIM-PS was subjected to 6 repeated experiments of preparing biodiesel by the esterification reaction described above. The experimental results showed that the conversion rate of oleic acid remained unchanged, indicating that H-PIM-PS has excellent stability. At the same time, the recovery rate of H-PIM-PS after the reaction is greater than 99%, indicating that H-PIM-PS has excellent reusability.
[0038] Example 4
[0039] H-PIM-PS was prepared using the same amino self-microporous polymer H-PIM-1 as in Example 1. 1 g of H-PIM-1 was dissolved in 50 mL of tetrahydrofuran and slowly added to 4.7525 g of 1,3-propane sultone using a constant pressure dropping funnel. The mixture was reacted at 50 °C for 24 h. After the reaction was completed, the mixture was poured into methanol for precipitation. After being repeatedly washed with methanol, the mixture was soaked in a 0.1 mol / L hydrochloric acid aqueous solution for 12 h to ensure that the sulfonic acid groups were H + The prepared catalyst H-PIM-PS was placed in a constant temperature drying oven at 60°C and dried for 12 hours. Finally, the self-microporous polymer acidic solid catalyst H-PIM-PS was obtained. The acid exchange capacity of H-PIM-PS was measured to be 1.59mmmol / g.
[0040] The catalyst H-PIM-PS prepared in this example was tested for its catalytic performance in catalyzing the production of biodiesel in an esterification reaction under the same reaction conditions as in Example 1. The results showed that the conversion rate of oleic acid was 89.9%. Then, H-PIM-PS was subjected to 6 repeated experiments of preparing biodiesel by the esterification reaction described above. The experimental results showed that the conversion rate of oleic acid remained unchanged, indicating that H-PIM-PS has excellent stability. At the same time, the recovery rate of H-PIM-PS after the reaction is greater than 99%, indicating that H-PIM-PS has excellent reusability.
[0041] Example 5
[0042] H-PIM-PS was prepared using the same amino self-microporous polymer H-PIM-1 as in Example 1. H-PIM-1 was dissolved in 50 mL of N,N-dimethylformamide and slowly added to 2.3762 g of 1,3-propane sultone using a constant pressure dropping funnel. The mixture was reacted at 60°C for 24 h. After the reaction was completed, the mixture was poured into methanol for precipitation. After being repeatedly washed with methanol, the mixture was soaked in a 0.1 mol / L hydrochloric acid aqueous solution for 12 h to ensure that the sulfonic acid groups were H + The prepared catalyst H-PIM-PS was placed in a constant temperature drying oven at 60°C and dried for 12 hours. Finally, the self-microporous polymer acidic solid catalyst H-PIM-PS was obtained. The acid exchange capacity of H-PIM-PS was measured to be 1.78mmmol / g.
[0043] The catalyst H-PIM-PS prepared in this example was tested for its catalytic performance in catalyzing the production of biodiesel in an esterification reaction under the same reaction conditions as in Example 1. The results showed that the conversion rate of oleic acid was 93.4%. Then, H-PIM-PS was subjected to 6 repeated experiments of preparing biodiesel by the esterification reaction described above. The experimental results showed that the conversion rate of oleic acid remained unchanged, indicating that H-PIM-PS has excellent stability. At the same time, the recovery rate of H-PIM-PS after the reaction was greater than 99%, indicating that H-PIM-PS has excellent reusability.
[0044] Example 6
[0045] The self-microporous polymer acidic solid catalyst was prepared by a method similar to that of Example 1, except that the degree of amination was changed to 20%. The acid exchange capacity of the self-microporous polymer acidic solid catalyst finally prepared was 0.62 mmmol / g, and the conversion rate of oleic acid was 63.8% under the same reaction conditions as in Example 1. This indicates that the degree of amination of the amino self-microporous polymer will affect the degree of sulfonation, thereby affecting the acid exchange capacity and catalytic performance of the self-microporous polymer acidic solid catalyst.
[0046] Example 7
[0047] The self-microporous polymer acidic solid catalyst was prepared by a method similar to that in Example 1, except that the reaction solvent was changed to 1,4-dioxane. The acid exchange capacity of the self-microporous polymer acidic solid catalyst finally prepared was 1.10 mmmol / g, and the conversion rate of catalytic oleic acid was 74.8% under the same reaction conditions as in Example 2. This indicates that changing the reaction solvent does not affect the acid exchange capacity and catalytic performance of H-PIM-PS.
[0048] Example 8
[0049] The self-microporous polymer acidic solid catalyst was prepared by a method similar to that in Example 1, except that the amount of tetrahydrofuran added was changed to 100 mL. The acid exchange capacity of the self-microporous polymer acidic solid catalyst finally prepared was 0.95 mmmol / g, and the conversion rate of oleic acid was 69.3% under the same reaction conditions as in Example 1. This indicates that the amount of solvent added does not affect the acid exchange capacity and catalytic performance of the prepared H-PIM-PS.
[0050] Example 9
[0051] A self-microporous polymer acidic solid catalyst was prepared by a method similar to Example 1, except that the temperature was changed to 70°C. The acid value of the finally prepared self-microporous polymer acidic solid catalyst was 1.26 mmmol / g, indicating that changing the reaction temperature will affect the degree of modification, and further affect the acid exchange capacity and catalytic performance of the catalyst.
[0052] Example 10
[0053] A self-microporous polymer acidic solid catalyst was prepared by a method similar to Example 1, except that 1,3-propanesulfonate was replaced by 1,4-butanesulfonate. The acid value of the finally prepared self-microporous polymer acidic solid catalyst was 1.22 mmmol / g, indicating that the type of sulfonate has little effect on the degree of modification.
[0054] The above-mentioned embodiment results show that the present invention selects a self-microporous polymer (H-PIM-1) with different degrees of ammoniation, and uses it as a raw material to modify and graft a large number of sulfonic acid groups, and utilizes the sulfonic acid groups to have catalytic activity in the esterification reaction of free fatty acids and short-chain alcohols. A self-microporous polymer acidic solid catalyst H-PIM-PS with excellent catalytic performance is prepared, and it is applied to the catalytic production of biodiesel, which can meet the actual industrial application requirements and is of great significance for the large-scale production of biodiesel.
[0055] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A method for preparing a self-microporous polymer acidic solid catalyst, characterized in that: The self-microporous polymer PIM-1 is dissolved in an organic solvent to obtain a PIM-1 solution, hydrazine hydrate is added to carry out a reduction reaction, and a self-microporous polymer H-PIM-1 with an amino group is synthesized; H-PIM-1 is reacted with sultone to synthesize a self-microporous polymer with a sulfonic acid group, and the self-microporous polymer acidic solid catalyst H-PIM-PS is obtained after washing and drying.
2. The method according to claim 1, characterized in that: The structural formula of H-PIM-1 is as follows: Wherein n=0.2%-100%.
3. The method according to claim 1, characterized in that: The organic solvent is one of tetrahydrofuran, 1,4-dioxane and N,N-dimethylformamide.
4. The method according to claim 1, characterized in that: The concentration of H-PIM-1 in the PIM-1 solution is 10-60 wt %.
5. The method according to claim 1, characterized in that: The sultone is 1,3-propanesultone or 1,4-butanesultone.
6. The method according to claim 1, characterized in that: The molar ratio of the repeating unit with amino group to sultone contained in H-PIM-1 is 1:1-20.
7. The method according to claim 1, characterized in that: The reaction temperature of H-PIM-1 and sultone is 30°C-70°C, and the reaction time is 4h-24h.
8. A self-microporous polymer acidic solid catalyst prepared by the method according to any one of claims 1 to 7.
9. Use of a self-microporous polymer acidic solid catalyst prepared by the method according to any one of claims 1 to 7 in catalyzing the preparation of biodiesel by esterification reaction.
Citation Information
Patent Citations
Multi-sulfonic acid funtionalized mesoporous polymeric solid acid catalyst and preparation method and application thereof
CN104815690A
Preparation method of solid type ionic liquid catalyst
CN109847798A
Preparation method of acidic solid catalyst
CN116462837A
Composite catalytic membrane applied to catalytic esterification and preparation method thereof
WO2012119294A1